Carbohydrates Comprehensive Studies on Glycobiology and Glycotechnology - Chang, Chuan-Fa (IntechOpen, 2012)
It is my great honor and pleasure to introduce this comprehensive book to readers who are interested in carbohydrates. This book contains 23 excellent chapters written by experts from the fields of chemistry, glycobiology, microbiology, immunology, botany, zoology, as well as biotechnology. According to the topics, methods and targets, the 23 chapters are further divided into five independent sections. In addition to the basic research, this book also offers much in the way of experiences, tools, and technologies for readers who are interested in different fields of Glycobiology. I believe that readers can obtain more than anticipated from this meaningful and useful book.